2019
DOI: 10.1155/2019/9734576
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Bioinformatics Analysis of Master Regulators in Anaplastic Thyroid Carcinoma

Abstract: Anaplastic thyroid carcinoma (ATC) is one of the most aggressive and rapidly lethal tumors. However, limited advances have been made to prolong the survival and to reduce the mortality over the last decades. Therefore, identifying the master regulators underlying ATC progression is desperately needed. In our present study, three datasets including GSE33630, GSE29265, and GSE65144 were retrieved from Gene Expression Omnibus with a total of 32 ATC samples and 78 normal thyroid tissues. A total of 1804 consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…After co-expression and correlation analysis using the Oncomine, bc-GenExMiner, and UCSC Xena web-based tools in the present study, we confirmed that CDC20 gene was positively correlated with BIRC5 expression. As a matter of fact, both CDC20 and BIRC5 were found to be co-expressed in lung adenocarcinoma, endometrial cancer, renal cell carcinoma, and thyroid carcinoma [31][32][33][34]. Given that cell cycle process is often coordinated with apoptotic proteins to maintain tissue homeostasis, silencing the expressions of cell cycle protein as well as anti-apoptotic proteins simultaneously could potentially lead to cell cycle arrest and reduce the proliferation of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…After co-expression and correlation analysis using the Oncomine, bc-GenExMiner, and UCSC Xena web-based tools in the present study, we confirmed that CDC20 gene was positively correlated with BIRC5 expression. As a matter of fact, both CDC20 and BIRC5 were found to be co-expressed in lung adenocarcinoma, endometrial cancer, renal cell carcinoma, and thyroid carcinoma [31][32][33][34]. Given that cell cycle process is often coordinated with apoptotic proteins to maintain tissue homeostasis, silencing the expressions of cell cycle protein as well as anti-apoptotic proteins simultaneously could potentially lead to cell cycle arrest and reduce the proliferation of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pan's study indicated that the hub genes showed inconsistent trends in ATC tissues, which may be due to the heterogeneity between cell line data and tumor tissue data. 52 So, only three of the five genes screened were validated in cell lines. The inconsistent results should be understandable.…”
Section: Dovepressmentioning
confidence: 99%
“…54 The top 10 DEGs with highest node degree were regarded as hub genes of ATC in Pan's study. 52 Hu's study did not do the screening with any of those screening methods. They simply get the top 10 hub genes by PPI network.…”
Section: Dovepressmentioning
confidence: 99%
“…Thyroid malignancy is commonly derived from stem of the thyroid follicular cells from epithelial, which can be additionally divided into the well distinguished malignancy cells, poorly discriminated malignance, and anaplastic malignance tumor cells rendering to the cancer behaviors. A distinguished thyroid malignancy cell is presently treated via thyroidectomy, succeeding radioactive iodine (RAI) treatment and long-standing thyroid triggering suppression of hormone (Bi et al., 2019 ; Corrigan et al., 2019 ; Ljubas et al., 2019 ; Pan et al., 2019 ). Although a majority of thyroid cancers have a favorable prognosis, there are scarcely any effective therapeutic approaches for metastatic thyroid cancers (Galofré et al., 2014 ; Kim et al., 2018 ; Ishihara et al., 2019 ; Janz et al., 2019 ; Wang et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%